Preparation method and application of microspheres, carbon microspheres, silicon-carbon microspheres, organic-inorganic composite microspheres and silicon dioxide microspheres
By forming a multi-layer shell structure on the phenolic resin microspheres, composite material microspheres with multi-layer morphology and multi-stage layered pore structure were prepared, which solved the problem of the lack of designability and structural diversity of existing materials, and realized that Efficient ion transport and material stability.
Patent Information
- Application Number
- CN202311082500.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
Existing nanoorganic and inorganic composite materials lack good design and structural diversity, making it difficult to show good application potential in multiple scenarios.
By forming a multi-layered shell structure on the surface of the phenolic resin microspheres, including a multi-stage layered micro/mesoporous structure composed of silica and phenolic resin, composite microspheres with multi-layered morphology were prepared.
The multi-layer structure and good designability of microspheres are realized, and a multi-stage pore structure is provided, which provides different active sites and fast channels for the diffusion and transport of ions, improving the energy storage efficiency and stability of the material.
Smart Images

Figure CN119503761A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon materials, and in particular to a preparation method and application of composite microspheres (organic-inorganic composite microspheres, silicon-carbon composite microspheres) and carbon microspheres and silicon dioxide microspheres derived therefrom. Background Art
[0002] Organic and inorganic composite materials are new materials formed by combining organic materials and inorganic materials in some way. The new composite materials have the advantages of organic and inorganic materials, and can give the materials many excellent properties in mechanical optics, thermal, electromagnetic and biological aspects. They are becoming one of the hot spots in materials science research. Nanocomposite materials are a new type of composite materials. It refers to a composite material composed of one or more components in the form of nano-scale particles, that is, particles close to the molecular level, compounded in a matrix. Nanocomposite materials are increasingly attracting attention because their dispersed phase size is in the transition zone between macroscopic and microscopic, which will bring special changes to the physical and chemical properties of the material. Nanomaterials are hailed as the most promising materials in the 21st century. The types of research on this type of materials have involved inorganic, organic and amorphous materials. Materials derived from nano-organic-inorganic composite materials show good design and can give derived materials different properties. However, the current nano-organic-inorganic composite materials are often prepared by compounding organic and inorganic materials, lacking good design and having a relatively simple structure.
[0003] In addition, with the continuous consumption of global petrochemical resources, a serious energy crisis has occurred, and a large amount of environmental pollution has also been caused. In this context, the application of new energy has received a lot of attention. For example, the use of clean energy such as wind energy, hydropower, and solar energy has been more widely popularized and applied. The storage and conversion of energy is an important basis for the application of clean energy. Devices such as batteries and supercapacitors provide a medium for the storage and conversion of clean energy, and are widely used in new energy vehicles, trucks, buses, electric bicycles and other transportation vehicles. Carbon materials, as the main component of energy storage and conversion devices, play an important role in the performance of storage and conversion devices. Among many carbon materials, carbon microspheres are used as electrode materials because of their rich pore structure, stable chemical composition, low density, uniform size distribution and other advantages, and have high power density and energy density.
[0004] Phenolic resin has the advantages of good thermal stability, high residual carbon, low cost, and easy pore formation, and is an ideal material for preparing carbon microspheres. Carbon microspheres with different morphologies and pore structures can be prepared with phenolic resin as the matrix, such as solid, hollow, shell-core and other microstructures, as well as micropores, mesopores and other pore structures. Micropores can create a large amount of surface area, which is conducive to the adsorption of ions, while mesopores have a larger size and can effectively promote the transmission of ions. The effective combination of micropores and mesopores can achieve multiple benefits. The shell-core structure, especially the soft yellow structure, is a special type of carbon microsphere with a certain cavity, as well as a core and shell with different structures inside and outside. As an electrode material, it has good energy storage efficiency. At present, the preparation methods of various types of shell-core structure carbon microspheres are mostly obtained under the regulation of surfactants. It is still a challenge to obtain shell-core or soft yellow structure mesoporous carbon microspheres without surfactants, and the preparation of mesoporous carbon microspheres with multi-level and hierarchical pore structures is a greater challenge. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a composite material microsphere with a multi-level structure, which has good designability, and to provide a derivative material based on the microsphere and a preparation method thereof, wherein the derivative material includes an organic-inorganic composite microsphere, a silicon-carbon microsphere, a carbon-silicon microsphere, and a silicon dioxide microsphere. The derivative material has a multi-level morphology and a multi-level layered micro / mesoporous structure, and has good application potential in various scenarios.
[0006] In order to solve the above technical problems, the present invention provides a microsphere, comprising an inner core formed of a phenolic resin, a first shell layer formed on the surface of the inner core, a second shell layer formed on the surface of the first shell layer, and a third shell layer formed on the surface of the second shell layer;
[0007] The first shell layer comprises silicon dioxide, the second shell layer comprises silicon dioxide and phenolic resin, and the third shell layer comprises phenolic resin.
[0008] Furthermore, the content of silicon dioxide in the second shell layer decreases gradually from the inside to the outside.
[0009] Further provided is a method for preparing microspheres, comprising:
[0010] The step of forming a phenolic resin core;
[0011] The step of forming a first shell layer composed of silicon dioxide on the surface of the phenolic resin core;
[0012] The step of forming a second shell layer composed of silicon dioxide / phenolic resin on the surface of the first shell layer;
[0013] And, forming a third shell layer composed of phenolic resin on the surface of the second shell layer.
[0014] Furthermore, the phenolic resin core is formed by a phenolic condensation reaction of phenol and aldehyde in a solvent and an alkaline catalyst.
[0015] Furthermore, the first shell layer is formed by hydrolysis and condensation of silicate in a solvent and an alkaline catalyst.
[0016] Furthermore, the second shell layer is formed by assembling a product of a phenol-formaldehyde condensation reaction between phenol and aldehyde in a solvent and an alkaline catalyst and a product of a hydrolysis condensation reaction of a silicate in the solvent and an alkaline catalyst.
[0017] Furthermore, the third shell layer is formed by a phenol-formaldehyde condensation reaction of phenol and aldehyde in a solvent and an alkaline catalyst under elevated temperature conditions.
[0018] Specifically, the preparation method comprises the following steps:
[0019] S1. Mixing phenol and an alkaline catalyst in a solvent to obtain a reaction solution;
[0020] S2, adding aldehyde to the reaction solution and stirring until turbid to obtain a turbid solution;
[0021] S3, adding silicate to the turbid liquid and reacting for 1 to 24 hours;
[0022] S4, heating the turbid liquid and reacting for 1 to 48 hours;
[0023] S5, separating, washing and drying the turbid liquid to obtain the microspheres.
[0024] Furthermore, the phenol is selected from at least one of resorcinol and 3-aminophenol.
[0025] Furthermore, the aldehyde is selected from formaldehyde or paraformaldehyde.
[0026] Furthermore, the alkaline catalyst is selected from at least one of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide and magnesium hydroxide.
[0027] Furthermore, the solvent is selected from at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.
[0028] Furthermore, the silicate is selected from at least one of tetraethyl silicate, tetrapropoxysilane, tetrabutyl silicate and tetraisopropyl orthosilicate.
[0029] Furthermore, the silicate is added to the reaction solution 1 to 16 hours after the reaction solution becomes turbid.
[0030] Furthermore, the phenolic resin is a pure phenolic resin or a doped phenolic resin composed of C, H, and O elements, and the doped phenolic resin contains at least one element of B, N, P, S, and the like.
[0031] Furthermore, the content of silicon dioxide in the second shell layer decreases gradually from the inside to the outside.
[0032] Further provided is an organic-inorganic composite microsphere prepared by the above-mentioned preparation method.
[0033] Further provided is a silicon-carbon microsphere, which is obtained by carbonizing the microsphere prepared by the above preparation method.
[0034] Further provided is a carbon microsphere, which is obtained by carbonizing the microsphere prepared by the above preparation method and removing silicon dioxide in sequence.
[0035] Further provided is a silicon dioxide microsphere, which is prepared by the above-mentioned preparation method and obtained by carbonization and decarbonization in sequence;
[0036] Alternatively, the microspheres are obtained by removing the phenolic resin.
[0037] The microspheres prepared by the above-mentioned preparation method are used in the preparation of electrode materials, molding materials, adsorption materials, drug-loaded materials or catalytic materials.
[0038] The beneficial effects of the present invention are as follows: the microspheres or organic-inorganic composite microspheres prepared by the present invention have a multi-level structure and good designability, and can be further designed to obtain functional silicon-carbon microspheres, carbon microspheres, silica microspheres and other derivatives. The carbon microspheres prepared by the present invention have a multi-level morphology, which can provide different active sites for the diffusion of ions. The microporous structure provides a large amount of surface area, which can create a large number of active sites for the attachment of ions. The mesoporous structure provides large holes, which provides a fast channel for the transmission of ions, effectively reduces the resistance of ion transmission, and promotes the efficient circulation of ions. The cavity in the core-shell structure can store a large amount of electrolyte and provide a large amount of medium for the transmission of ions. The outer microporous structure protects the morphology of the carbon microspheres and can effectively improve the stability of the carbon microspheres. The supercapacitor electrode prepared with the carbon microspheres has high capacity, good rate performance and cycle stability performance, and is an ideal material for preparing electrodes. The multi-layered core-shell organic-inorganic composite microspheres prepared by the method are carbonized to obtain silicon-carbon composite microspheres, which have a stable spherical morphology and are ideal precursors for preparing silicon-carbon negative electrode materials. After removing carbon from silicon-carbon microspheres or removing phenolic resin from organic-inorganic composite microspheres, hollow multi-shell silica microspheres are obtained, which have low metal ion content, large cavities and double-shell structures, and can be used in food, medicine, electronics and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of the organic-inorganic composite microspheres prepared in Example 1 of the specific implementation manner of the present invention;
[0040] Figure 2 This is a SEM image of silicon-carbon microspheres prepared in Example 1 of the specific implementation manner of the present invention;
[0041] Figure 3 TEM image of carbon microspheres prepared in Example 1 of the specific implementation mode of the present invention;
[0042] Figure 4 This is a TEM image of the silica microspheres prepared in Example 1 of the specific embodiment of the present invention;
[0043] Figure 5 This is a schematic diagram of the structure of multi-layer core-shell organic-inorganic composite microspheres in a specific embodiment of the present invention;
[0044] Figure 6 It is a schematic diagram of the structure of multi-level hierarchical mesoporous phenolic carbon microspheres in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0045] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.
[0046] In the present invention, the difference between the condensation reaction rate of phenolic aldehyde and the hydrolysis condensation rate of silicate is utilized to make phenolic aldehyde react preferentially and condense to prepare the phenolic resin microsphere inner core. Then silicate is added, because of its faster reaction rate and high initial concentration, rapid hydrolysis condensation forms a large amount of silicon dioxide particles and is coated on the outside of the phenolic resin microsphere inner core alone to form the first shell of silicon dioxide. As the concentration of silicate decreases, the reaction rate is more matched with the condensation reaction rate of phenolic aldehyde, thus, the silicon dioxide produced by the hydrolysis condensation of silicate and the phenolic resin produced by the condensation of phenolic aldehyde will be assembled together and coated on the outside of the first shell of silicon dioxide to form the second composite shell. Since the hydrolysis condensation rate and reaction degree of silicate are higher than phenol / aldehyde, as the reaction is further carried out, the silicate has been substantially reacted, and the remaining phenol and aldehyde in the system will continue to react to form phenolic resin, which is coated on the surface of the second composite shell to form the third shell, and finally the organic-inorganic composite microsphere of multi-shell core structure is obtained. Due to the gradual decrease in the concentration of silicate reaction, the silicon dioxide in the second composite shell layer presents a gradient distribution from concentrated to diluted from the inside to the outside.
[0047] The organic-inorganic composite microspheres show good designability. After carbonization, the organic-inorganic composite microspheres are obtained to obtain silicon-carbon composite core-shell microspheres, the core is carbon, the first shell is silicon dioxide, the second shell is a silicon dioxide / carbon composite layer, and the third shell is carbon. At the same time, under the confinement and protection of the first shell of silicon dioxide, the inner layer of phenolic resin carbonizes and shrinks to form a cavity. After removing silicon dioxide, the cavity size is further increased, and a mesoporous shell layer with a graded pore structure with a gradient distribution, as well as a microporous core and a microporous outermost shell layer are obtained. After removing carbon from silicon-carbon microspheres or removing phenolic resin from organic-inorganic composite microspheres, hollow multi-shell silica microspheres are obtained, and the wall layer has a layered structure, with a dense inner layer and a loose outer layer.
[0048] Specifically, the present invention provides a microsphere and a preparation method thereof. The microsphere comprises an inner core formed of a phenolic resin, a first shell layer formed on the surface of the inner core, a second shell layer formed on the surface of the first shell layer, and a third shell layer formed on the surface of the second shell layer; wherein the composition of the first shell layer comprises silicon dioxide, the composition of the second shell layer comprises silicon dioxide and a phenolic resin, and the composition of the third shell layer comprises a phenolic resin. The preparation method comprises: a step of forming an inner core of a phenolic resin microsphere; a step of forming a first shell layer composed of silicon dioxide on the surface of the inner core of the phenolic resin microsphere; a step of forming a second shell layer composed of silicon dioxide / phenolic resin on the surface of the first shell layer; and a step of forming a third shell layer composed of a phenolic resin on the surface of the second shell layer. The inner core of the phenolic resin microsphere is formed by a phenol-formaldehyde condensation reaction between phenol and aldehyde in a solvent and an alkaline catalyst, the first shell is formed by hydrolysis and condensation of silicate in a solvent and an alkaline catalyst, the second shell is formed by assembling a product of a phenol-formaldehyde condensation reaction between phenol and aldehyde in a solvent and an alkaline catalyst, and the third shell is formed by a phenol-formaldehyde condensation reaction between phenol and aldehyde in a solvent and an alkaline catalyst under a heating condition. The microsphere can prepare derivatives such as silicon-carbon microspheres, carbon microspheres, and silica microspheres, and the noble metal catalyst based on the carbon microspheres shows good designability and functionality.
[0049] Furthermore, the preparation method comprises the following steps:
[0050] S1. Mixing phenol and an alkaline catalyst in a solvent to obtain a reaction solution;
[0051] S2, adding aldehyde to the reaction solution and stirring until turbid to obtain a turbid solution;
[0052] S3, adding silicate to the turbid liquid and reacting for 1 to 24 hours;
[0053] S4, heating the turbid liquid and reacting for 1 to 48 hours;
[0054] S5, separating, washing and drying the turbid liquid to obtain the microspheres.
[0055] Specifically, phenol and aldehyde react in a solvent and under the action of an alkaline catalyst to form a phenolic resin microsphere core; then silicate is added, and the silica produced by the rapid hydrolysis of the silicate is first coated on the surface of the phenolic resin microsphere core to form a first silica shell; then the silica produced by the further hydrolysis of the silicate and the phenolic resin particles are assembled and coated outside the first silica shell to form a second shell; finally, phenol and aldehyde continue to react to form a phenolic resin coated outside the second shell to form a third shell, to obtain a multi-layered core-shell organic-inorganic composite microsphere; the multi-layered core-shell organic-inorganic composite microsphere is carbonized to obtain a silicon-carbon microsphere; the silicon-carbon microsphere removes silica to obtain a multi-layered hierarchical mesoporous carbon microsphere; the silicon-carbon microsphere removes carbon to obtain a hollow multi-shell silica microsphere. Furthermore, the multi-layered core-shell organic-inorganic composite microsphere can also be directly removed from the phenolic resin to obtain a hollow multi-shell silica microsphere, and the removal method can be a physical method or a chemical method, such as dissolving the phenolic resin with a solvent, or removing the phenolic resin by high-temperature burning. It should be noted that dissolving the phenolic resin by a solvent method or removing the phenolic resin by high-temperature burning are both conventional technical means in the art and will not be elaborated here.
[0056] More specifically, at least one of the silicate such as tetraethyl silicate, tetrapropoxysilane, tetrabutyl silicate and tetraisopropyl orthosilicate has a rapid hydrolysis condensation rate in a solvent under the action of an alkaline catalyst, and can quickly form silica microspheres, which is an effective method for preparing monodisperse silica. The condensation rate of phenol and aldehyde is relatively slow. Specifically, the phenol such as one or a combination of two of resorcinol and 3-aminophenol, and the aldehyde such as formaldehyde or paraformaldehyde, react relatively slowly between them. Taking tetraethyl silicate and resorcinol and formaldehyde as examples, if they are added to the reaction system (solvent and alkaline catalyst system) at the same time, tetraethyl silicate will first react to form a silica core, and then the phenolic resin formed by the condensation of resorcinol and formaldehyde is coated on the silica surface, and after carbonization and removal of silica, hollow carbon microspheres with a microporous structure can be obtained. Therefore, in order to obtain the carbon microspheres of the present invention, we first put phenol and aldehyde into the reaction system, so that they are preferentially condensed to form the core of the phenolic resin microspheres, and then add silicate. However, due to the extremely fast reaction rate of silicate, phenol and aldehyde have reacted for a period of time, the concentration decreases, and the reaction rate is further reduced. Therefore, the silica produced by the hydrolysis and condensation of silicate at high concentration will be assembled and coated on the surface of the phenolic resin microspheres to form a confined protective layer, the main component of which is silica. When the concentration of silicate decreases, the hydrolysis and condensation rate decreases, and the silica particles produced by it and the phenolic resin particles will be assembled and coated on the surface of silica together, thereby forming a second shell layer, which is a composite layer of silica and phenolic resin. After the reaction continues, the silicate has basically reacted, and the remaining phenol and aldehyde in the system further condense to form a phenolic resin layer, which will be coated outside the composite shell layer to form a third shell layer, the main component of which is phenolic resin.
[0057] In order to obtain the third shell layer, the reaction conditions of S4 can be adjusted, such as increasing the reaction temperature, increasing the reaction time, etc. to promote the further condensation reaction of the remaining phenol and aldehyde to form the third shell layer. The relative concentrations of phenol and aldehyde can also be increased so that both phenol and aldehyde remain in the later stage, thereby forming the third shell layer.
[0058] In combination with the specific preparation method, phenol and aldehyde are preferentially introduced into the system, the system is composed of a solvent and a catalyst, further, the catalyst is one or two or more of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide, magnesium hydroxide, preferably an ammonia / amine catalyst, the ammonia / amine catalyst is ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine or hexamethylenetetramine, more preferably ammonia water, diethylamine or hexamethylenetetramine. The solvent is one or more of water, ethanol, methanol, acetone, tetrahydrofuran, methane, chloroform, more preferably water, ethanol or methanol or a combination thereof.
[0059] The most critical point in preparing the multi-layer core-shell organic-inorganic composite microspheres, multi-layer graded mesoporous soft yellow shell carbon microspheres, and hollow multi-shell silica microspheres of the present invention is that phenol and aldehyde react preferentially in the system until turbidity appears, and then silicate is added. The timing of adding silicate can be selected at different times after the appearance of turbidity. If it is added earlier, the phenolic resin core will be smaller and the composite shell will be thicker. If it is added later, the phenolic resin core will be larger and the composite shell will be thinner. However, the time of adding silicate cannot be too late. It needs to be added under the condition that there is enough phenol and aldehyde content in the system and phenolic resin particles can be formed, so that it can be assembled and coated with phenolic resin to form a composite shell. Preferably, silicate can be added 1 to 16 hours after turbidity appears.
[0060] Whether there are residual phenol and aldehyde in the system and how much their content is related to the amount of phenol and aldehyde put into the system. Preferably, the concentration of the phenol in the solution is 0.3-200 mg / mL, more preferably 1-25 mg / mL. The amount of phenol directly affects the particle size of the inner core microsphere and the thickness of the third shell layer. The larger the amount of phenol, the larger the particle size of the inner core microsphere formed, and the thicker the third shell layer. The amount of phenol also affects the reaction rate. The reaction rate is large at high concentrations, and vice versa. Under different phenol dosage conditions, the timing of adding silicate can be adjusted so that a composite shell layer can be formed, and the present invention does not impose specific restrictions on it.
[0061] The time and degree of reaction of phenol and aldehyde to form turbidity are also related to the amount of aldehyde added, but the amount of aldehyde required is as long as microspheres can be formed. Preferably, the molar ratio of phenol to aldehyde is preferably 1:1 to 10, more preferably 1:1 to 3. A high amount of aldehyde can accelerate the reaction rate, so that turbidity is formed earlier, and the particle size of the formed phenolic resin microspheres is relatively small. The amount of aldehyde needs to be selected according to the size or preparation efficiency of the prepared carbon microspheres, but it does not affect the formation of the carbon microspheres of the present invention.
[0062] As a simple raw material of the present invention, hexamethylenetetramine can be directly used to replace the alkaline catalyst and aldehyde. Aldehyde and ammonia can be decomposed in the solution of hexamethylenetetramine to participate in the condensation reaction of phenolic formaldehyde. The amount of the catalyst also affects the reaction rate and ultimately affects the particle size, shell core size, etc. of the microspheres. Preferably, the mass ratio of the alkaline catalyst to phenol is 0.1 to 20:1. When ammonia water, diethylamine or hexamethylenetetramine is preferred, the mass ratio of the alkaline catalyst to phenol can be further preferably 0.5 to 5:1.
[0063] Further reaction (S4) is a key factor in forming the third shell layer. It is preferred to increase the reaction temperature to obtain the third shell layer. In the previous reaction, the silicate has basically reacted, and the phenol and aldehyde have also reacted to a certain extent. At a higher temperature, the phenol and aldehyde further condense to form a phenolic resin that is coated alone in the outermost layer. The reaction temperature is preferably 60 to 250° C., more preferably 80 to 160° C. Different reaction temperatures affect the thickness of the third shell layer and the formation time of the third shell layer. At high temperatures, the shell layer is thick and the formation time of the shell layer is short. At low temperatures, the shell layer is thin and the formation time of the shell layer is long.
[0064] Under the action of alkaline catalyst, and under the controlled raw material addition time, a shell core microsphere with a multilayer shell structure can be formed, wherein the kernel is a phenolic resin, the first shell layer is mainly silicon dioxide, the second shell layer is a composite layer of phenolic resin and silicon dioxide, and the third shell layer is mainly phenolic resin. The formation of the first shell layer is the key shell layer to obtain the soft yellow structure of the present invention. The formation of the shell layer is formed in the first reaction stage after the silicate is put into the silicate. It is a dense shell layer formed based on the rapid hydrolysis and condensation of silicate at the initial concentration. This shell layer has good thermal stability and plays a spatial confinement role to the phenolic resin kernel during the carbonization process, so that the kernel shrinks to form a cavity during carbonization. At the same time, the silica shell layer (first shell layer) also protects the kernel, suppresses the inward contraction of the outer layer, and is conducive to the formation of the cavity.
[0065] The microspheres or organic-inorganic composite microspheres are formed after carbonization to form multi-shell silicon-carbon microspheres, the core is carbon, which is converted from carbonization of phenolic resin, the first shell is silicon dioxide, there is a cavity between the first shell and the core, the second shell is a composite layer of silicon dioxide and carbon, which is converted from a composite layer of silicon dioxide / phenolic resin, and the third shell is carbon, which is converted from carbonization of phenolic resin. After further removal of silicon dioxide, the first shell disappears, the size of the cavity is further expanded, the second shell forms mesopores, and the core and the third shell are micropores. The second shell makes the carbon microspheres present a hierarchical pore structure due to the gradient distribution of silicon dioxide. Preferably, the method for removing silicon dioxide can be solvent etching.
[0066] The rich pore structure, hierarchical multi-level morphology, controllable cavities and sizes provide good application prospects for the carbon microspheres in the fields of electrode materials, thermal insulation, adsorption, etc. Therefore, the multi-level hierarchical mesoporous phenolic carbon microspheres have application potential in the preparation of electrode materials, molding materials, adsorption materials, drug-loaded materials or catalytic materials.
[0067] In one embodiment, the phenolic resin is a pure phenolic resin or a doped phenolic resin composed of C, H, and O elements, and the doped phenolic resin is doped with at least one element of B, N, P, S, and the like.
[0068] In one embodiment, the content of silicon dioxide in the second shell layer decreases gradually from the inside to the outside, that is, the content of silicon dioxide in the second shell layer presents a gradient distribution from concentrated to diluted from the inside to the outside.
[0069] Further provided is an organic-inorganic composite microsphere prepared by the above-mentioned preparation method.
[0070] Further provided is a silicon-carbon microsphere, which is obtained by carbonizing the microsphere prepared by the above preparation method.
[0071] Further provided is a carbon microsphere, which is obtained by carbonizing the microsphere prepared by the above preparation method and removing silicon dioxide in sequence.
[0072] Further provided is a silicon dioxide microsphere, which is prepared by the above-mentioned preparation method and obtained by carbonization and decarbonization in sequence;
[0073] Alternatively, the microspheres are obtained by removing the phenolic resin.
[0074] The microspheres prepared by the aforementioned preparation method provide good application prospects for the carbon microspheres in the fields of electrode materials, thermal insulation, adsorption, etc. due to their rich pore structure, hierarchical multi-level morphology, controllable cavities and sizes. Therefore, the multi-level hierarchical mesoporous phenolic carbon microspheres have application potential in the preparation of electrode materials, molding materials, adsorption materials, drug-loaded materials or catalytic materials.
[0075] Example 1
[0076] A method for preparing microspheres comprises the following steps:
[0077] S1: Add 0.4 g of resorcinol, 3 mL of ammonia water, and water / ethanol (10 mL / 70 mL) into the reactor and stir evenly;
[0078] S2, adding 0.59 g of 37% (M / V) formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 140 min;
[0079] S3, adding 3.5 mL of tetrapropoxysilane to the reaction solution of step S2, and continuing the reaction for 24 h;
[0080] S4, raising the reaction temperature to 100°C, allowing the reaction solution in step S3 to continue reacting for 24 hours;
[0081] S5, after separation, washing and drying, the multi-layered core-shell organic-inorganic composite microspheres (RF@RF / SiO 2 @RF)(Structural diagram as shown Figure 5 shown);
[0082] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres (C@C / SiO 2 @C);
[0083] S62, silicon carbon microspheres are treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C1 (schematic diagram as shown in Figure 6 shown);
[0084] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0085] SEM( Figure 1 ) shows that the composite microspheres (RF@RF / SiO 2 @RF) has a spherical appearance with a diameter of about 789nm, and a large number of small particles can be seen on the surface. After carbonization, the SEM image ( Figure 2 ) Visible silicon carbon microspheres (C@C / SiO 2 @C) still maintains the original spherical shape, with a diameter of about 721nm, and the volume is reduced by about 24% compared with the microspheres. After removing the silicon dioxide with HF, the carbon microspheres were obtained. TEM shows ( Figure 3 ) The obtained carbon microsphere (C1) is a soft yellow shell structure with a double shell. The core size is about 306nm, the shell thickness is about 193nm, of which the first shell thickness is 176nm, the second shell thickness is 17nm, and there is a less obvious and narrow cavity between the first shell and the core, with an average cavity size of about 11nm. It can be further seen that the first shell is radial from the inside to the outside, while the second shell is relatively dense, with a rough surface and slightly undulating. The above results show that the prepared carbon microsphere is a soft yellow shell structure carbon microsphere with a double shell, and its precursor RF@RF / SiO 2 @RF is also a core-shell structure. The mesopore diameter of the carbon microspheres calculated by nitrogen adsorption / desorption test results is 16nm, and there are micropores. The BET specific surface area and pore volume are 851.4m 2 and 1.9cm 3 ·g -1 .
[0086] Silicon carbon microspheres (C@C / SiO 2 @C) After burning in air to remove carbon, silicon microspheres were obtained. TEM ( Figure 4) It can be seen that the silicon microspheres present a hollow structure with a spherical appearance and a diameter of about 679nm, which is comparable to the diameter of the first shell core layer of the carbon microspheres, and there is no second shell layer. This further indicates that the second shell layer and the main core component carbon of the silicon-carbon composite carbon microspheres are removed after burning in the air, and the first shell layer is a silicon-carbon composite layer. Further observations found that the thickness of the silicon microsphere core layer is about 179nm, slightly larger than the thickness of the first shell core layer of the carbon microspheres. High-magnification TEM further shows that the silicon microspheres also present radial shapes, and silicon dioxide is distributed in a gradient, with dense distribution in the inner layer and gradually becoming thinner outward.
[0087] Example 2
[0088] S1. Add 0.4 g of resorcinol, 3 mL of ammonia water, and water / ethanol (10 mL / 70 mL) into the reactor and stir evenly;
[0089] S2, adding 0.59 g of 37% formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 140 min;
[0090] S3, adding 2.8 mL of tetraethyl silicate to the reaction solution of step S2, and continuing the reaction for 24 h;
[0091] S4, raising the reaction temperature to 100°C, allowing the reaction solution in step S3 to continue reacting for 24 hours;
[0092] S5, after separation, washing and drying, multi-layered core-shell organic-inorganic composite microspheres are obtained;
[0093] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres;
[0094] S62, silicon carbon microspheres were treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C2;
[0095] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0096] Example 3
[0097] S1. Add 0.4 g of resorcinol, 3 g of ammonia water, and water / ethanol (10 mL / 70 mL) into a reactor and stir evenly;
[0098] S2, adding 0.59 g of 37% formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 140 min;
[0099] S3, add 1.4 mL of tetraethyl silicate and 1.73 mL of tetrapropoxysilane to the reaction solution of step S2, and continue the reaction for 24 h;
[0100] S4, raising the reaction temperature to 100°C, allowing the reaction solution in step S3 to continue reacting for 24 hours;
[0101] S5, after separation, washing and drying, multi-layered core-shell organic-inorganic composite microspheres are obtained;
[0102] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres;
[0103] S62, silicon carbon microspheres were treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C3;
[0104] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0105] Example 4
[0106] S1. Add 0.6 g of resorcinol, 3 mL of ammonia water, and water / ethanol (15 mL / 105 mL) into the reactor and stir evenly;
[0107] S2, adding 0.9 g of 37% formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 160 min;
[0108] S3, adding 5 mL of tetraethoxysilane to the reaction solution of step S2, and continuing the reaction for 24 h;
[0109] S4, raising the reaction temperature to 100°C, allowing the reaction solution in step S3 to continue reacting for 24 hours;
[0110] S5, after separation, washing and drying, multi-layered core-shell organic-inorganic composite microspheres are obtained;
[0111] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres;
[0112] S62, silicon carbon microspheres were treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C4;
[0113] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0114] Example 5
[0115] S1. Add 0.8 g of resorcinol, 5 mL of ammonia water, and water / ethanol (20 mL / 140 mL) into a reactor and stir evenly;
[0116] S2, adding 1.2 g of 37% formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 160 min;
[0117] S3, adding 11 mL of tetraethyl silicate to the reaction solution of step S2, and continuing the reaction for 24 h;
[0118] S4, raising the reaction temperature to 120°C, allowing the reaction solution of step S3 to continue reacting for 24 hours;
[0119] S5, after separation, washing and drying, multi-layered core-shell organic-inorganic composite microspheres are obtained;
[0120] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres;
[0121] S62, silicon carbon microspheres were treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C5;
[0122] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0123] Example 6
[0124] S1. Add 0.6 g of resorcinol, 2.1 mL of ammonia water, and water / ethanol (15 mL / 105 mL) into a reactor and stir evenly;
[0125] S2, adding 0.9 g of 37% formaldehyde to the reaction solution of step S1, reacting until turbidity appears, and continuing the reaction for 160 min;
[0126] S3, adding 5.5 mL of tetraethyl silicate to the reaction solution of step S2, and continuing the reaction for 24 h;
[0127] S4, raising the reaction temperature to 140°C, allowing the reaction solution of step S3 to continue reacting for 24 hours;
[0128] S5, after separation, washing and drying, multi-layered core-shell organic-inorganic composite microspheres are obtained;
[0129] S61, multi-layer core-shell organic-inorganic composite microspheres were carbonized at 700℃ for 4h to obtain silicon-carbon microspheres;
[0130] S62, silicon carbon microspheres were treated with hydrofluoric acid to remove silicon dioxide to obtain multi-level hierarchical mesoporous carbon microspheres C6;
[0131] S63. Silicon carbon microspheres are burned in air to remove carbon and obtain hollow multi-shell silica microspheres.
[0132] Test example
[0133] The multi-level hierarchical mesoporous carbon microspheres prepared in Examples 1 to 6 were subjected to supercapacitor performance tests, and the electrical performance test results are shown in Table 1.
[0134] Supercapacitor performance test: Carbon microspheres were mixed evenly with binder PVDF and carbon black in a mass ratio of 8:1:1, coated on nickel foam electrode sheets to make working electrodes, and constant current charge and discharge tests were performed.
[0135] Table 1
[0136]
[0137]
[0138] It can be seen from Table 1 that the electrode prepared using the multi-level hierarchical mesoporous phenolic carbon microspheres obtained in the present invention as a material has high capacity and capacity retention rate, and is an ideal electrode material.
[0139] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A microsphere, characterized in that: It comprises an inner core formed of phenolic resin, a first shell layer formed on the surface of the inner core, a second shell layer formed on the surface of the first shell layer, and a third shell layer formed on the surface of the second shell layer; The first shell layer comprises silicon dioxide, the second shell layer comprises silicon dioxide and phenolic resin, and the third shell layer comprises phenolic resin.
2. A method for preparing microspheres, characterized in that: include: The step of forming a phenolic resin core; The step of forming a first shell layer composed of silicon dioxide on the surface of the phenolic resin core; The step of forming a second shell layer composed of silicon dioxide / phenolic resin on the surface of the first shell layer; And, forming a third shell layer composed of phenolic resin on the surface of the second shell layer.
3. The preparation method according to claim 2, characterized in that: The content of silicon dioxide in the second shell layer decreases gradually from the inside to the outside.
4. The preparation method according to claim 2, characterized in that: The phenolic resin core is formed by a phenolic condensation reaction of phenol and aldehyde in a solvent and an alkaline catalyst.
5. The preparation method according to claim 2, characterized in that: The first shell layer is formed by hydrolysis and condensation of silicate in a solvent and a basic catalyst.
6. The preparation method according to claim 2, characterized in that: The second shell layer is a product of a phenol-formaldehyde condensation reaction between phenol and aldehyde in a solvent and an alkaline catalyst, and is assembled together with a product of a hydrolysis condensation reaction between silicate and the solvent and an alkaline catalyst.
7. The preparation method according to claim 2, characterized in that: The third shell layer is formed by a phenol-formaldehyde condensation reaction of phenol and aldehyde in a solvent and an alkaline catalyst under elevated temperature conditions.
8. The preparation method according to claim 4, 6 or 7, characterized in that: The phenol is selected from at least one of resorcinol and 3-aminophenol.
9. The preparation method according to claim 4, 6 or 7, characterized in that: The aldehyde is selected from formaldehyde or paraformaldehyde.
10. The preparation method according to claim 4, 6 or 7, characterized in that: The alkaline catalyst is selected from at least one of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide and magnesium hydroxide.
11. The preparation method according to any one of claims 4 to 7, characterized in that: The solvent is selected from at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.
12. The preparation method according to claim 5 or 6, characterized in that: The silicate is selected from at least one of tetraethyl silicate, tetrapropoxysilane, tetrabutyl silicate and tetraisopropyl orthosilicate.
13. An organic-inorganic composite microsphere, characterized in that: The compound is prepared by the preparation method according to any one of claims 2 to 12.
14. A silicon-carbon microsphere, characterized in that: The microspheres prepared by the preparation method according to any one of claims 2 to 12 are obtained by carbonization.
15. A carbon microsphere, characterized in that: The microspheres prepared by the preparation method according to any one of claims 2 to 12 are obtained by carbonizing and removing silicon dioxide in sequence.
16. A silica microsphere, characterized in that: The microspheres prepared by the preparation method according to any one of claims 2 to 12 are obtained by carbonization and decarbonization in sequence; Alternatively, the microspheres are obtained by removing the phenolic resin.
17. Use of the microspheres prepared by the preparation method according to claim 2 in preparing electrode materials, molding materials, adsorption materials, drug-loaded materials or catalytic materials.